2015
DOI: 10.1002/adma.201500040
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/Si‐Quantum‐Dot Heterojunction Diodes Showing High Photosensitivity Compatible with Quantum Confinement Effect

Abstract: Graphene/Si quantum dot (QD) heterojunction diodes are reported for the first time. The photoresponse, very sensitive to variations in the size of the QDs as well as in the doping concentration of graphene and consistent with the quantum-confinement effect, is remarkably enhanced in the near-ultraviolet range compared to commercially available bulk-Si photodetectors. The photoresponse proves to be dominated by the carriertunneling mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…Figure 6), assuming the same sensing mechanism as previously reported for a graphenesemiconductor hybrid phototransistor. [9][10][11][12][13] By contrast, a high photoresponse was observed with visible light illumination, suggesting a new sensing mechanism in our phototransistor. Figure 1b shows the photocurrent (after dark current subtraction) of the as-prepared AgX-G photodetectors at room temperature under chopped light illumination (white light illumination with a power of~54.9 nW) at a 1-V source-drain voltage (V SD ) and a 0-V back-gate voltage (V G ).…”
Section: Photodetector Design Device Fabrication and Temporal Photormentioning
confidence: 75%
See 2 more Smart Citations
“…Figure 6), assuming the same sensing mechanism as previously reported for a graphenesemiconductor hybrid phototransistor. [9][10][11][12][13] By contrast, a high photoresponse was observed with visible light illumination, suggesting a new sensing mechanism in our phototransistor. Figure 1b shows the photocurrent (after dark current subtraction) of the as-prepared AgX-G photodetectors at room temperature under chopped light illumination (white light illumination with a power of~54.9 nW) at a 1-V source-drain voltage (V SD ) and a 0-V back-gate voltage (V G ).…”
Section: Photodetector Design Device Fabrication and Temporal Photormentioning
confidence: 75%
“…By contrast, graphene hybrid phototransistors [4][5][6][7][8] provide high photoresponsivity by incorporating a layer of light absorbing material, such as a layer of semiconducting quantum dots (QDs), [9][10][11][12][13] which is in contact with the graphene. Upon illumination, the photoexcited carriers in the QDs can be injected into graphene while the charged QDs layer can modulate the conductance of graphene by capacitive coupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For large responsivity, graphene should be used as a contact, not as a photo-active element. Several studies [53,57,[76][77][78][79][80][81][82] on the photodetecting potential of graphene heterojunctions have shown that careful selection of materials allows for significant enhancement of responsivity by up to $10 orders of magnitude (see Fig. 2b).…”
Section: Visible and Ultravioletmentioning
confidence: 99%
“…Silicon (Si) nanostructures are attracting considerable attention for a wide range of applications1, 2, 3, 4, 5, 6 due to their fascinating and highly complex properties 7, 8, 9. For instance, efficient photoluminescence (PL) from crystalline Si quantum dots (i.e., with diameter less than ≈5 nm) has been reported, which encourages their applications in optoelectronic devices such as light‐emitting diodes10 or in biomedical applications as fluorescent tags 11.…”
mentioning
confidence: 99%